2020
DOI: 10.5812/jjnpp.95301
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Extracellular Matrix by Scrophularia striata Extract in Vitro: A Potential Antiscarring Agent

Abstract: Background: Hypertrophic scars are the consequences of the aberration of normal wound healing. To date, therapeutic strategies for abnormal scarring have been unsuccessful. ‎‏The abnormal extracellular‎ matrix is one of the most important contributing factors to ‎hypertrophic scars. ‏Scrophularia striata has been used in Iranian folk medicine for the treatment of burn wounds. ‏The plant extract accelerates wound healing and attenuates scar formation. Objectives: The study was performed to investigate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In this study, we evaluated the effects of topical and intralesional injection of S. striata on MMP2 and MMP9 gene expression, and our results revealed that topical, but not intralesional, injection of SSE stimulated MMP2 and MMP9 expression in scar tissue samples. Our previous study also showed that SSE stimulates MMP1 expression at the mRNA and protein levels in cultured fibroblasts [ 15 ]. The role of MMP2 and MMP9 in scarless wound healing has been demonstrated in a study by Dang et al (2003) [ 26 ], in which scarless fetal wound healing was associated with an increase in the MMPs to tissue-derived MMP inhibitor ratio.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, we evaluated the effects of topical and intralesional injection of S. striata on MMP2 and MMP9 gene expression, and our results revealed that topical, but not intralesional, injection of SSE stimulated MMP2 and MMP9 expression in scar tissue samples. Our previous study also showed that SSE stimulates MMP1 expression at the mRNA and protein levels in cultured fibroblasts [ 15 ]. The role of MMP2 and MMP9 in scarless wound healing has been demonstrated in a study by Dang et al (2003) [ 26 ], in which scarless fetal wound healing was associated with an increase in the MMPs to tissue-derived MMP inhibitor ratio.…”
Section: Discussionmentioning
confidence: 94%
“…The wound healing effects of S. striata have been evaluated in human and animal models of ulcers and burns [ 10 , 14 ]. Based on the anti-inflammatory and antioxidant properties as well as the modulatory effects of SSE on ECM [ 15 ], in this study, we investigated the effects of S. striata in the prevention and treatment of HSs in a rabbit ear model of HSs.…”
Section: Introductionmentioning
confidence: 99%
“…The plant was dried and grounded to a fine powder. The plant hydroalcoholic (ethanol/distilled water 7/3 v/v) extract was prepared by using maceration method (24) .…”
Section: Preparation Of S Striata Extractmentioning
confidence: 99%